Do the chairman's political promotion incentive influence the investment efficiency: Evidence from SOEs in China - Han, Yuntong (2022)
In the background of China's unique transition economy, this study selects the listed state-owned enterprises in China from 2012 to 2021 as a sample. The main objective of this research will be to reveal the impact of the chairman's political promotion incentive on the inefficient investment of state-owned enterprises, as well as the adjustment effect of the chairman's equity incentive and the state-owned enterprise equity mix on this impact. Based on principal-agent, information asymmetry and government intervention theory, this study performs systematic GMM estimation and multiple regression by constructing panel data models. The empirical results show that the chairman's political promotion incentive will increase the inefficient investment in state-owned enterprises, while the higher equity incentive and the proportion of state-owned shares will curb this impact. In conclusion, this study finds that when the political promotion incentives are significant, the chairmen prefer to obtain the promotion opportunity by achieving the political goals and thus deviate from the optimal investment decision, leading to inefficient investment in the state-owned enterprises.